Multidimensional MR spectroscopic imaging of prostate cancer in vivo. (31st July 2013) - Thomas, M. Albert; Nagarajan, Rajakumar; Huda, Amir; Margolis, Daniel; Sarma, Manoj K.; Sheng, Ke; Reiter, Robert E.; Raman, Steven S.
<x xml:space="preserve">Abstract</x> Prostate cancer (PCa) is the second most common type of cancer among men in the United States. A major limitation in the management of PCa is an inability to distinguish, early on, cancers that will progress and become life threatening. One‐dimensional (1D) proton (1H) MRS of the prostate provides metabolic information such as levels of choline (Ch), creatine (Cr), citrate (Cit), and spermine (Spm) that can be used to detect and diagnose PCa. Ex vivo high‐resolution magic angle spinning (HR‐MAS) of PCa specimens has revealed detection of more metabolites such as myo‐inositol (mI), glutamate (Glu), and glutamine (Gln). Due to the J‐modulation and signal overlap, it is difficult to quantitate Spm and other resonances in the prostate clearly by single‐ and multivoxel‐based 1D MR spectroscopy. This limitation can be minimized by adding at least one more spectral dimension by which resonances can be spread apart, thereby increasing the spectral dispersion. However, recording of multivoxel‐based two‐dimensional (2D) MRS such as J‐resolved spectroscopy (JPRESS) and correlated spectroscopy (L‐COSY) combined with 2D or three‐dimensional (3D) magnetic resonance spectroscopic imaging (MRSI) using conventional phase‐encoding can be prohibitively long to be included in a clinical protocol. To reduce the long acquisition time required for spatial encoding, the echo‐planar spectroscopic imaging (EPSI) technique has been combined with correlated spectroscopy to give four‐dimensional (4D) echo‐planar correlated spectroscopic imaging (EP‐COSI) as well as J‐resolved spectroscopic imaging (EP‐JRESI) and the multi‐echo (ME) variants. Further acceleration can be achieved using non‐uniform undersampling (NUS) and reconstruction using compressed sensing (CS). Earlier versions of 2D MRS, theory of 2D MRS, spectral apodization filters, newer developments and the potential role of multidimensional MRS in PCa detection and management will be reviewed here. Copyright © 2013 John Wiley & Sons, Ltd.